2020
DOI: 10.22495/cocv17i3art14
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management and debt maturity: Evidence from Italy

Abstract: In this work, we examine whether earnings management affects the debt maturity structure of Italian non-SMEs. We employ accruals quality as a proxy for earnings management. We measure the accrual quality as the absolute value of residual reflects the accruals that are not related to cash flow realized in the current, following or previous year. We measure the debt maturity in two ways. First, we consider it as a dummy variable that takes the value equal to 1 if some of the debt is long-term (exceeding one year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Companies that practice earnings management through discretionary accruals (showing lower earnings quality) impact debt contracts granted by lenders. The results of this study are also in line with (Rey et al, 2020) and (De Meyere et al, 2018), which found that companies with higher earnings quality tend to have a larger proportion of long-term debt. The quality of earnings reported by the company will affect the quality of financial reporting as a whole.…”
Section: Theoretical Reviewsupporting
confidence: 88%
See 4 more Smart Citations
“…Companies that practice earnings management through discretionary accruals (showing lower earnings quality) impact debt contracts granted by lenders. The results of this study are also in line with (Rey et al, 2020) and (De Meyere et al, 2018), which found that companies with higher earnings quality tend to have a larger proportion of long-term debt. The quality of earnings reported by the company will affect the quality of financial reporting as a whole.…”
Section: Theoretical Reviewsupporting
confidence: 88%
“…Profits of companies that can better predict future cash flows can reduce information asymmetry between creditors and debtors to increase the company's ability to access long-term debt. This finding is in line with (Maurice et al, 2020) and (Rey et al, 2020), which shows that companies that carry out aggressive earnings management activities tend to have lower long-term debt structures. However, the results of studies on the effect of earnings quality on debt maturity are still contradictory.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations